Validation of the brief scale for the evaluation of acculturation stress in migrant population (EBEA) - Urzúa, Alfonso (2021)
Background: Acculturation stress is associated with poorer physical and mental health and a lower level of psychological well-being. The causes of acculturation stress are diverse, but most are similar in the migrant population. Despite the importance of evaluating this variable, few studies have reported culturally adapted and validated instruments for specific populations. Based on this, the aim of this study was to evaluate the psychometric properties of a short scale for the evaluation of acculturation stress (EBEA). Methods: Two studies were conducted, involving 1725 first-generation Colombian and Peruvian migrants living in Chile, between the ages of 18 and 60 years. In addition to the EBEA and as evidence of validity, the Beck Anxiety Scale and the WHOQOL-BREF psychological health domain were applied. A confirmatory factor analysis was carried out, and the reliability and nomological validity were evaluated. Results: The results in both studies indicated that the scale presents a factorial structure of three dimensions: (a) the stress derived from the preparation and departure from the country of origin, (b) the stress produced by socioeconomic concerns in the host country, and (c) the tensions typical of adaptation to sociocultural changes or Chilean society. The reliability coefficients and the analysis of their nomological validity were very good. Conclusions: The EBEA is a measure that offers quick, useful screening for researchers who need a short measure for research among migrants. This tool contributes to the work of education, prevention, and intervention in the field of general health and migrants’ mental health.